LITERATURE REVIEW: WHY USE ROLEPLAY METHOD INTEACHING SPEAKING? - Manda Negara, Irma (LPPM STBA Pontianak, 2021)
The roleplay method is one of the methods proven to improve students' speaking ability. This study aims to provide a more in-depth explanation of the use of the roleplay method in learning English to improve students' speaking skills. This research is a literature study by carrying out stages in the form of searching and finding relevant data, analyzing the data found, and expressing ideas from these findings. This study examines the understanding of the roleplay method, the procedure for implementing the roleplay method, and the impact of the roleplay method, especially in improving students' speaking skills. Based on the results, it was found that the roleplay method can improve students' speaking skills, increase self confidence, collaboration among students, and make the learning atmosphere fun and interesting.